Influence of the probiotic preparation “Plantarum” in the diets of pregnant animals on the growth and development of young animals - Funk Irina (EDP Sciences, 2021)
The work aims to study the effect of different doses of the experimental probiotic preparation “Plantarum” when fed to pregnant animals on their reproductive qualities, as well as on the growth and development of young animals. To obtain young animals, four groups of goats were formed in the type of the Saanen breed, 20 heads each. In the first (control) group, the animals received a standard diet, in the diet of the animals of the second, third and fourth groups in the second half of pregnancy, the probiotic preparation “Plantarum” was additionally introduced, containing Lactobacillus Plantarum, Propiobacterium freudenreihii, in dosages from 0.4 to 0.8 ml/kg of body weight per day. From the offspring of the goats of the experimental groups, four groups of 12 goats were formed. The highest percentage of preservation (94%) and the highest business output of kids per 100 queens (150%) were observed in the fourth experimental group (0.8 ml). The goats of the second, third and fourth groups exceeded the body weight of their contemporaries from the control group by 3%, 6.3%, and 8.8%. The highest indices of the absolute increase in body weight by age periods were noted in the fourth group of goats. There were no significant differences in body build indices during the experiment between the goats of the control and experimental groups. Thus, the maximum positive effect was observed with the introduction of a probiotic preparation into the diet of pregnant goats at a dose of 0.8 ml/kg of body weight per day.